CoaTx-II, a new dimeric Lys49 phospholipase A2 from Crotalus oreganus abyssus snake venom with bactericidal potential: Insights into its structure and biological roles. (15th September 2016) - Almeida, J.R.; Lancellotti, M.; Soares, A.M.; Calderon, L.A.; Ramírez, D.; González, W.; Marangoni, S.; Da Silva, S.L.
Abstract: Snake venoms are rich and intriguing sources of biologically-active molecules that act on target cells, modulating a diversity of physiological functions and presenting promising pharmacological applications. Lys49 phospholipase A2 is one of the multifunctional proteins present in these complex secretions and, although catalytically inactive, has a variety of biological activities, including cytotoxic, antibacterial, inflammatory, antifungal activities. Herein, a Lys49 phospholipase A2, denominated CoaTx-II from Crotalus oreganus abyssus, was purified and structurally and pharmacologically characterized. CoaTx-II was isolated with a high degree of purity by a combination of two chromatographic steps; molecular exclusion and reversed-phase high performance liquid chromatography. This toxin is dimeric with a mass of 13868.2 Da (monomeric form), as determined by mass spectrometry. CoaTx-II is rich in Arg and Lys residues and displays high identity with other Lys49 PLA2 homologues, which have high isoelectric points. The structural model of dimeric CoaTx-II shows that the toxin is non-covalently stabilized. Despite its enzymatic inactivity, in vivo CoaTx-II caused local muscular damage, characterized by increased plasma creatine kinase and confirmed by histological alterations, in addition to an inflammatory activity, as demonstrated by mice paw edema induction and pro-inflammatory cytokine IL-6 elevation. CoaTx-II also presents antibacterial activity against gram negative ( Pseudomonas aeruginosa 31NM, Escherichia coli ATCC 25922) and positive ( Staphyloccocus aureus BEC9393 and Rib1) bacteria. Therefore, data show that this newly purified toxin plays a central role in mediating the degenerative events associated with envenomation, in addition to demonstrating antibacterial properties, with potential for use in the development of strategies for antivenom therapy and combating antibiotic-resistant bacteria. Graphical abstract: Highlights: CoaTx-II is a basic Lys49 PLA2 homologue from Crotalus oreganus abyssus snake venom. The primary structure and quaternary of CoaTx-II were studied. CoaTx-II was not able to hydrolyze micelar and non-micelar substrates. CoaTx-II, although enzymatically inactive showed bactericidal potential. CoaTx-II caused both local myotoxicity and edema, with an increase in IL-6 levels.